Cyclic growth of hierarchical structures in the aluminum-silicate system - Dyonizy, Agnieszka; Kaminker, Vitaliy; Wieckowska, Joanna; Krzywicki, Tomasz; Pantaleone, Jim; Nowak, Piotr; Maselko, Jerzy (Journal of systems chemistry, 2015)
Background Biological structures grow spontaneously from a seed, using materials supplied by the environment. These structures are hierarchical, with the ‘building blocks’ on each level constructed from those on the lower level. To understand and model the processes that occur on many levels, and later construct them, is a difficult task. However interest in this subject is growing. It is now possible to study the spontaneous growth of hierarchical structures in simple, two component chemical systems. Results Aluminum-silicate systems have been observed to grow into structures that are approximately conical. These structures are composed of multiple smaller cones with several hierarchical levels of complexity. On the highest level the system resembles a metropolis, with a horizontal resource distribution network connecting vertical, conical structures. The cones are made from many smaller cones that are connected together forming a whole with unusual behavior. The growth is observed to switch periodically between the vertical and horizontal directions. Conclusion A structure grown in a dish is observed to have many similarities to other hierarchical systems such as biological organisms or cities. This system may provide a simple model system to search for universal laws governing the growth of complex hierarchical structures. Graphical Abstract Side view of the chemical structure made from many vertical cones to form a chemical metropolis. The tallest structure is 17 cm high.